Preparation, Photoelectricity Property and Photocatalytic Activity of Alkaline-Earth Metals Modified TiO2 Nanoparticles - Min, Zong-Yi; Liu, Shao-You; He, Zhong-Bing; Liu, Yun-Guo; Zeng, Guang-Ming; Hu, Xin-Jiang; Liu, Si-Mian; Nie, Xin (Asian Journal of Chemistry, 2014)
To find the properties of the IIA main group elements (MeIIA) modified titanium dioxide (TiO2) nanomaterials, MeIIA (MeIIA = Be, Mg, Ca, Sr, Ba) modified TiO2 (MeIIA-TiO2) nanoparticles were successfully prepared by solid state reaction method. Moreover, the microstructure, surface photovoltaic properties and photocatalytic properties of the materials were characterized. The results showed that, except for Ba element, the other IIA metals doped TiO2 nanomaterials were anatase. MeIIA-TiO2 materials’ micromorphology was spherical nanoparticles and their size distributions were gradually widened with the increase of ionic radius and mass fraction. In addition, UV-visible spectra were red-shifted and approached about 410 nm. Under the same conditions, it was positive that photocatalytic degradation experience of fenvalerate and photoelectric conversion ability of MeIIA-TiO2 nanomaterials, following an order of Ca-TiO2 > Sr-TiO2 > Ba-TiO2 > Mg-TiO2 > Be-TiO2. However, its quantum efficiency was in order: Ca-TiO2 > Ba-TiO2 > Mg- TiO2 > Sr-TiO2 > Be-TiO2> TiO2.